Neurocoagulation from a Mechanistic Point of View in the Central Nervous System - Shavit-Stein, Efrat; Berkowitz, Shani; Gofrit, Shany Guly; Altman, Keren; Weinberg, Nitai; Maggio, Nicola (Seminars in Thrombosis and Hemostasis, 2022)
Coagulation mechanisms are critical for maintaining homeostasis in the central nervous system (CNS). Thrombin, an important player of the coagulation cascade, activates protease activator receptors (PARs), members of the G-protein coupled receptor family. PAR1 is located on neurons and glia. Following thrombin activation, PAR1 signals through the extracellular signal-regulated kinase pathway, causing alterations in neuronal glutamate release and astrocytic morphological changes. Similarly, the anticoagulation factor activated protein C (aPC) can cleave PAR1, following interaction with the endothelial protein C receptor. Both thrombin and aPC are expressed on endothelial cells and pericytes in the blood-brain barrier (BBB). Thrombin-induced PAR1 activation increases cytosolic Ca2+ concentration in brain vessels, resulting in nitric oxide release and increasing F-actin stress fibers, damaging BBB integrity. aPC also induces PAR1 activation and preserves BBB vascular integrity via coupling to sphingosine 1 phosphate receptors. Thrombin-induced PAR1 overactivation and BBB disruption are evident in CNS pathologies. During epileptic seizures, BBB disruption promotes thrombin penetration. Thrombin induces PAR1 activation and potentiates N-methyl-D-aspartate receptors, inducing glutamate-mediated hyperexcitability. Specific PAR1 inhibition decreases status epilepticus severity in vivo. In stroke, the elevation of brain thrombin levels further compromises BBB integrity, with direct parenchymal damage, while systemic factor Xa inhibition improves neurological outcomes. In multiple sclerosis (MS), brain thrombin inhibitory capacity correlates with clinical presentation. Both thrombin inhibition by hirudin and the use of recombinant aPC improve disease severity in an MS animal model. This review presents the mechanisms underlying the effects of coagulation on the physiology and pathophysiology of the CNS.
Keywords: PARs; thrombin; activated protein C; stroke; epilepsy; multiple sclerosis